System for CT‐guided needle placement in the thorax and abdomen: A design for clinical acceptability, applicability and usability. Issue 1 (5th December 2017) - Arnolli, Maarten M.; Buijze, Martijn; Franken, Michel; de Jong, Koert P.; Brouwer, Dannis M.; Broeders, Ivo A. M. J.
Abstract: Background: Various systems exist for CT‐guided needle placement in the thorax and abdomen, but widespread adoption is lacking. The goal of this work is to develop a system for precise needle placement with a design focus on clinical acceptability, applicability and usability. Methods: A system was outlined incorporating a needle guide on a mechanism with a remote centre of motion, manually placeable around the patient at the desired entry point and lockable by push‐button to the CT table. System and patient are scanned for system‐to‐CT registration and target specification. The needle guide is automatically aimed at the target, for manual needle insertion to specified depth. Results: A fully functional prototype was realized, achieving 1.2±0.6 mm placement error at 79.0±8.4 mm depth and 2.1±0.7 mm at 156.0±6.9 mm for 2×12 in‐ and out‐of‐plane punctures in a gelatin phantom. Conclusions: The system enables precise needle placement in a single insertion and is ready for its first clinical deployment.